2019
DOI: 10.36300/remasp.2019.016
|View full text |Cite
|
Sign up to set email alerts
|

La influencia de la vegetación acuática en el desarrollo de las poblaciones de "Simulium erythrocephalum" (De Geer, 1776) (Diptera, Simuliidae) en Madrid: su relación con las emergencias masivas de mosca negra.

Abstract: Muchas especies de mosca negra (Diptera, Simuliidae) son causantes de picaduras en humanos y en ganado, con importantes consecuencias desde el punto de vista médico y veterinario, principalmente cuando son vectores de diferentes enfermedades infecciosas. En este trabajo hemos abordado la importancia que tienen los macrófitos acuáticos presentes en los ríos como sustrato para las etapas preimaginales de la especie Simulium erythrocephalum. En España esta especie causa molestas picaduras en humanos y, durante l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 7 publications
0
11
0
3
Order By: Relevance
“…Submerged macrophytes are phanerogamic plants that live rooted or not on the river bed and maintain their entire structure underwater, being able to grow to occupy large extensions of the river bed [19]. This association between the massive proliferation of macrophytes and blackflies has also been observed in other Spanish regions affected by this pest [2,14,[20][21][22]. This relationship of macrophyte-blackfly larvae was observed again in 2012 in the Ebro River in the vicinity of Zaragoza [23].…”
Section: Discussionmentioning
confidence: 87%
“…Submerged macrophytes are phanerogamic plants that live rooted or not on the river bed and maintain their entire structure underwater, being able to grow to occupy large extensions of the river bed [19]. This association between the massive proliferation of macrophytes and blackflies has also been observed in other Spanish regions affected by this pest [2,14,[20][21][22]. This relationship of macrophyte-blackfly larvae was observed again in 2012 in the Ebro River in the vicinity of Zaragoza [23].…”
Section: Discussionmentioning
confidence: 87%
“…Comparing to the Segura river (Sánchez et al, 2018) with just 1 species found or the Amadorio river (López-Peña and Jiménez-Peydró, 2020) with 2 species, 3 species have been found in the Jarama and Tajo rivers (Soriano et al, 2019), 4 in the Ebro river (Ruiz-Arrondo et al, 2017) (Puig et al, 1984), Monegre (López-Peña and Jiménez-Peydró, 2020) rivers and Molinos stream (Ricoy-Llavero, 2015), 8 species in the Guadalhorce, Guadiaro (González et al, 1987), Lozoya (Casado et al, 1990), Anllóns, Eo, Lérez, Mandeo, Masma, Mera, Ouro, Pereira, Sar, Ulla and Umia (Lestón et al, 2014), Manzanares (Soriano et al, 2019) and Algar (López-Peña and Jiménez-Peydró, 2020) rivers and Orcera stream (Ricoy-Llavero, 2015), 9 in the Besós, Foix (González, 1985) and Cidacos (Ruiz and Rubio, 1999) rivers, while 10 species (S. angustipes, S. argyreatum, S. equinum, S. erythrocephalum, S. intermedium, S. lineatum, S. ornatum, S. petricolum, S. trifasciatum and S. velutinum) were identified in the present study in the Tormes river. This shows this is one of the most diverse rivers, after the Serpis river with 14 species (López-Peña and Jiménez-Peydró, 2020), Mijares (López-Peña and Jiménez-Peydró, 2018), Yeguas (González et al, 1986) and Ter (Puig et al, 1987) rivers with 13 species in each.…”
Section: Discussionmentioning
confidence: 96%
“…The haematophagous species of medical and veterinary concern identified in the present study should be taken in great consideration due to the fact that they have been reported as the cause of bites and painful derived pathologies that endanger the health of both humans and animals. Concerning S. erythrocephalum, an anthropophilic species, cases of outbreaks and massive attacks on humans have been reported (Ignjatović-Ćupina et al, 2006), with a negative impact on the public health services when they occur (López-Peña et al, 2021a;Ruiz-Arrondo et al, 2017;Soriano et al, 2019), since the primary care department of health centres and hospitals can be overwhelmed, providing health care as a result of the bites received and the concomitant allergic reactions (Anonymous, 2013). What is more, the inconvenience caused by these insects to humans and animals can lead to economic depreciation in the tourist and livestock sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde 1995 hasta la actualidad, los simúlidos como plaga han venido adquiriendo una gran relevancia en ciertas regiones del territorio español. En concreto, las comunidades más afectadas han sido Aragón, Cataluña, Madrid y la Comunidad Valenciana (Gallego et al, 1994;Villanúa-Inglada et al, 2013;Ruiz Arrondo et al, 2014López-Peña, 2018b;Soriano Hernando et al, 2019), pero recientemente se han sumado otras regiones como Murcia (Sánchez López et al, 2018) y Andalucía (Obregón Romero et al, 2016;Ricoy-Llavero et al, 2020). En nuestro estudio, las especies del grupo S. ornatum y del subgénero Wilhelmia fueron las más abundantes, hecho que podría estar relacionado con la elevada tolerancia a la polución de ambos grupos, pudiendo sustituir a otras especies cuando hay un incremento de materia orgánica en el agua (Ciadamidaro et al, 2016).…”
Section: Punto Subgénerounclassified